2017
DOI: 10.1186/s13099-017-0206-9
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Salmonella enterica and Escherichia coli in raw chicken and beef meat in northern Egypt and dissemination of their antibiotic resistance markers

Abstract: BackgroundThe global incidence of foodborne infections and antibiotic resistance is recently increased and considered of public health concern. Currently, scarcely information is available on foodborne infections and ESBL associated with poultry and beef meat in Egypt.MethodsIn total, 180 chicken and beef meat samples as well as internal organs were collected from different districts in northern Egypt. The samples were investigated for the prevalence and antibiotic resistance of Salmonella enterica serovars an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
65
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 66 publications
17
65
4
Order By: Relevance
“…The prevalence of Salmonella in feces and carcasses found in this study was very high when compared to other studies. Moawad et al (2017) The 90% Salmonella prevalence in carcasses reported in our study is also not unexpected considering the unhygienic conditions and practices observed at the vending sites. It is very likely that cross-contamination during handling and preparation leads to carcasses contamination and Ingmer (2011) reported in their study that applying good cleaning and sanitization practices could effectively reduce Salmonella spp.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The prevalence of Salmonella in feces and carcasses found in this study was very high when compared to other studies. Moawad et al (2017) The 90% Salmonella prevalence in carcasses reported in our study is also not unexpected considering the unhygienic conditions and practices observed at the vending sites. It is very likely that cross-contamination during handling and preparation leads to carcasses contamination and Ingmer (2011) reported in their study that applying good cleaning and sanitization practices could effectively reduce Salmonella spp.…”
Section: Discussionsupporting
confidence: 72%
“…Moawad et al. () reported recovery of Salmonella in 8.3% of the poultry carcasses in Egypt, and Odoch et al. () reported Salmonella in 21.3% of the poultry feces in Uganda.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of genetic element such as integrons is often associated with multi-resistant phenotypes among Salmonella isolates and plays an important role in spread of antimicrobial resistance genes among gram-negarive bacteria [40]. In this study, class 1 integron detected in 26.9% of Salmonella isolates, which was higher than that previously study from raw chicken and beef meat in Egypt (13.3%) [36] and from poultry in Korea (9.1 ) [41], but lower when compared with a report from meat and dairy products in Egypt (39.1 ) [32]. The predominant gene cassette was dfrA17-aadA5 which conferring resistance to trimethoprim (dfrA) and spectinomycin (aadA) and has been reported worldwide in isolates from different origins, might be associated with the extensive use of trimethoprim and spectinomycin in broiler breeding.…”
Section: Discussioncontrasting
confidence: 50%
“…In this study, aac(6')-Ib-cr, oqxB, qnrB, and qnrD genes were detected in 26.9%, 13.4 , 9.0 and 1.5 respectively in all Salmonella isolates, which was different from the report in Henan province, qnrA, qnrB, qnrS and aac(6')-Ib-cr genes were identifified in Salmonella strains isolated from retail foods with the incidence of 46.6%, 12.7%, 19.5 , and 13.6 , respectively [35]. In other study, in Egypt, qnrA, qnrB, and qnrS genes were detected in 33.3 , 20.0 and 6.7 , respectively in all Salmonella isolates from raw chicken and beef meat [36].…”
Section: Discussionmentioning
confidence: 73%
“…There was no Salmonella isolation from L, S, K (as edible offal in our country) and GB (possible responsible organ for chronic NTS carriage) samples from slaughtered cattle (Table ). Within a limited number of studies investigating Salmonella prevalence in slaughter cattle including internal organs, Im, Seo, Bae, and Lee (), and Lee and Lee () could not detect Salmonella in 6 and 8 livers in Korea, respectively, while Moawad et al () found 10% contamination rate in both of their 10 liver and 10 spleen samples in Egypt. Also, Alemu and Zewde () from Ethiopia and Genç () from Turkey found 1.1% (2/181 samples) and 0.4% (1/250 samples) Salmonella in their liver and spleen samples, respectively.…”
Section: Discussionmentioning
confidence: 94%